2016
DOI: 10.1007/s00253-016-7532-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a multi-species biofilm model and metatranscriptomic analysis of biofilm and planktonic cell communities

Abstract: We collected several biofilm samples from Japanese rivers and established a reproducible multi-species biofilm model that can be analyzed in laboratories. Bacterial abundance at the generic level was highly similar between the planktonic and biofilm communities, whereas comparative metatranscriptomic analysis revealed many upregulated and downregulated genes in the biofilm. Many genes involved in iron-sulfur metabolism, stress response, and cell envelope function were upregulated; biofilm formation is mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…Studies that link structure and function of phototrophic biofilms on a molecular level are rare, yet the few existing studies report a composition of organisms and gene expression under stable conditions that is a broadly similar to our results (Krohn‐Molt et al., ; Nakamura et al., ; Schneider, Reimer, Hahlbrock, Arp, & Daniel, ). In a recent study, Lindemann and colleagues investigated protein expression patterns during succession in cyanobacterial biofilms (Lindemann et al., ).…”
Section: Resultssupporting
confidence: 89%
“…Studies that link structure and function of phototrophic biofilms on a molecular level are rare, yet the few existing studies report a composition of organisms and gene expression under stable conditions that is a broadly similar to our results (Krohn‐Molt et al., ; Nakamura et al., ; Schneider, Reimer, Hahlbrock, Arp, & Daniel, ). In a recent study, Lindemann and colleagues investigated protein expression patterns during succession in cyanobacterial biofilms (Lindemann et al., ).…”
Section: Resultssupporting
confidence: 89%
“…BCAAs, which include valine, leucine, and isoleucine, may also contribute to fatty acid synthesis, which is also a feature of cancer metabolism (57). Valine and/or leucine secretion were previously associated with E. coli (58) and polymicrobial environmental biofilms (59). Polyamines were previously shown through metabolomics to be increased in CRC patients, with a rare polyamine, N1, N12-diacetylspermine detected in biofilm-positive CRCs (60), and we found that multiple microbial polyamine-related genes were increased in BFϩT mice (61).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the initial step for biofilm formation is the attachment of the planktonic cells to the surface to become sessile cells and trigger the development of the biofilm. Cells that form biofilms and planktonic cells have differences in gene expression, such as those involved in lipid metabolism, metabolite production, carbohydrate and amino acid transport, stress response, and iron‐sulfur metabolism (Nakamura et al., ). Regarding iron metabolism, the expression of certain adhesion factors that are crucial for initial cell attachment to the surface are induced by a high concentration of iron in the environment (Berlanga & Guerrero, ).…”
Section: Quorum Sensingmentioning
confidence: 99%